Nilai-Nilai Moderasi Beragama Dalam Buku Teks Siswa Mata Pelajaran Pai Dan Budi Pekerti Jenjang SMA - Samsul Fajri; Khairul Amri; Azizah Hanum OK (Journal on Education, 2024)
This study aims to analyze the representation and cultivation of religious moderation values in the textbooks of students of Islamic Religious Education (PAI) and Budi Pekerti High School (SMA) subjects. The research method used is content analysis to explore the textbook content of PAI and Budi Pekerti students from various publishers commonly used in high schools. The study found that PAI textbooks emphasize moderate understanding and practice of Islamic teachings, with an emphasis on the values of tolerance, justice, and interfaith harmony. However, there are variations in the presentation of religious moderation, in which some textbooks may accentuate the dogmatic side without leaving room for more inclusive interpretations. Meanwhile, Budi Pekerti textbooks pay attention to the character and moral development of students, including values of religious moderation such as mutual respect, empathy, and social responsibility. However, there is a tendency to ignore certain aspects of religious moderation, such as the integration of beliefs into everyday life. The results of this study provide an overview of the extent to which religious moderation values are included in the high school curriculum, especially in PAI and Budi Pekerti subjects. The implications of these findings could be used as a basis for the development of a more balanced and inclusive curriculum, promoting a better understanding of religious moderation among younger generations.